Seduction men, masculinity, and mediated intimacy - O'Neill, Rachel (Polity, 2018)
In the first book-length study of the so-called 'seduction community', Rachel O'Neill goes beyond established understandings of 'pickup artists' as pathetic, pathological, or perverse, and examines what makes the industry so compelling for those drawn into its folds"--